Rheumatic mitral stenosis based on Wilkins score and echo score revisited for patients undergoing balloon mitral valvuloplasty - Prayoga Setiawan; Ni Made Ayu Wulan Sari; Luh Oliva Saraswati Suastika; Ida Bagus Rangga Wibhuti (DiscoverSys Inc., 2021)
Background: An important factor for obtaining good results with good clinical outcomes from BMV procedure in rheumatic mitral stenosis is selecting the right candidate. This study aimed to determine rheumatic mitral stenosis characteristics based on conventional scoring system and echo score revisited for patients undergoing balloon mitral valvuloplasty.Method: This was a retrospective descriptive study with a cross-sectional approach. The study was conducted at the Department of Cardiology and Vascular Medicine, Sanglah Hospital Denpasar. Data were collected between January 1, 2019 and December 31, 2019 from registry and medical records.Result: Both groups had the same median age, which is 43 years old. The majority of research subjects were female, namely 16 people or 94.4%. There were no subjects from the failed group who had low echo score revisited. A total of 3 subjects (100.0%) with Wilkins score of 7 and high echo score revisited categorized as failed because of occurrence of significant mitral regurgitation post-procedure. In the successful group with Wilkins score of 8, there were no subjects who had a low echo score revisited value. In subjects with a Wilkins score of 8 and high echo score revisited value, 3 subjects categorized as failed and 1 subject obtained significant mitral regurgitation post-procedure.Conclusion: Patients with a low Wilkins score, but a high echo score revisited had a higher procedure failure rate.